2012
DOI: 10.1292/jvms.11-0374
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Immunohistochemical Studies of Subclinical Infection of Chicken Anemia Virus in 4-Week-Old Chickens

Abstract: ABSTRACT. Subclinical infection of chicken anemia virus (CAV) at 4 to 6 weeks of age, after maternal antibodies have waned, is implicated in several field problems in broiler flocks. In order to understand the pathogenesis of subclinical infection with CAV, an immunopathological study of CAV-inoculated 4-week-old SPF chickens was performed. Sixty 4-week-old SPF chickens were equally divided into CAV and control groups. The CAV group was inoculated intramuscularly with the MSB1-TK5803 strain of CAV. Neither mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Similarly, flow cytometric analysis of peripheral blood lymphocytes indicated significant decrease of CD4 + CD8 -and CD4 -CD8 + cells in the chicks of CIAV infected group. Such destructive effects on lymphoid organs in adult infected chicks were observed immunohistochemically by other workers during subclinical infection (Smyth et al, 2006;Haridy et al, 2012a). The blood CD4 + CD8 -:CD4 -CD8 + ratio was low (1-1.2: 1) as compared to 1.2-3.25 ratio which may be due to SPF nature of the chicks.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Similarly, flow cytometric analysis of peripheral blood lymphocytes indicated significant decrease of CD4 + CD8 -and CD4 -CD8 + cells in the chicks of CIAV infected group. Such destructive effects on lymphoid organs in adult infected chicks were observed immunohistochemically by other workers during subclinical infection (Smyth et al, 2006;Haridy et al, 2012a). The blood CD4 + CD8 -:CD4 -CD8 + ratio was low (1-1.2: 1) as compared to 1.2-3.25 ratio which may be due to SPF nature of the chicks.…”
Section: Discussionmentioning
confidence: 58%
“…All these changes were in agreement with the previous reports Latheef et al, 2013). Recent findings have shown that in the adult susceptible birds, CIAV replicates at high concentration in the thymus, and causes characteristic histopathological changes in the thymus, spleen, bursa of Fabricius, proventriculus and caecal tonsils (Kaffashi et al, 2006;Haridy et al, 2012a;Wani et al, 2014). Infections with CIAV increases the susceptibility of birds to secondary (bacterial/viral) infections, depresses vaccinal immunity, aggravates residual pathogenicity of attenuated virus and vaccine strains leading to vaccination failures and various disease outbreaks (Pope, 1991;Adair et al, 1993;Todd, 2000;Dhama et al, 2003;Dhama et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adair et al [77] reported that CD3 1 CD8 1 TCRαβ spleen cells constitute the major CIAV-infected population in the spleen. Recently, Haridy et al [78] reported that infection in 4-week-old chickens resulted in a moderate loss of CD4 1 and CD8 1 cells in the spleen and thymus. Infection in 1-day-old chicks causes a more severe depletion of CD4 1 and CD8 1 cells (e.g., [79]).…”
Section: Chicken Infectious Anemia Virusmentioning
confidence: 99%